Developmental Alterations of Cerebral Gray and White Matter in Children with Congenital Cyanotic Heart Disease - Leon-Wyss, Juan; Rosario, Cynthia; Toribio, Janet; Speckter, Herwin; Foerster, Bernd; Oviedo, Jairo; Huppertz, Hans-Jürgen; Stoeter, Peter (Journal of Pediatric Neurology, 2019)
This article examines the relation between oxygen saturation and T2 star time in cyanotic congenital heart disease and its correlation to cerebral gray and white matter alterations. Magnetic resonance imaging was performed in 25 patients (mean age: 52.2 months) and 32 controls. Gray and white matter volumes, as well as fractional anisotropy and longitudinal diffusivity, were significantly reduced in patients. The reduction longitudinal diffusivity correlated to oxygen saturation and T2 star time of gray matter (p < 0.05). This diffusion tensor imaging (DTI) parameter was most affected in cyanotic congenital heart disease and because is the only parameter showing significant correlation to reduced oxygenation, it should be included more often in the follow-up of these patients over time.
Keywords: developmental heart disease; oxygenation; T2 star time; diffusion tensor imaging